Synthesis and Biological Evaluation of Oxindole Sulfonamide Derivatives as Bruton's Tyrosine Kinase Inhibitors - Koraboina, Chandra Prakash; Maddipati, Venkatanarayana Chowdary; Annadurai, Narendran; Gurská, Soňa; Džubák, Petr; Hajdúch, Marián; Das, Viswanath; Gundla, Rambabu (ChemMedChem, 2024)
Bruton's tyrosine kinase (BTK) is a promising molecular target for several human B-cell-related autoimmune disorders, inflammation, and haematological malignancies. The pathogenic alterations in various cancer tissues depend on mutant BTK for cell proliferation and survival, and BTK is also overexpressed in a range of hematopoietic cells. Due to this, BTK is emerging as a potential drug target to treat various human diseases, and several reversible and irreversible inhibitors have been developed and are being developed. As a result, BTK inhibition, clinically validated as an anticancer treatment, is finding great interest in B-cell malignancies and solid tumours. This study focuses on the design and synthesis of new oxindole sulfonamide derivatives as promising inhibitors of BTK with negligible off-target effects. The most cytotoxic compounds with greater basicity were PID-4 (2.29±0.52 μM), PID-6 (9.37±2.47 μM), and PID-19 (2.64±0.88 μM). These compounds caused a selective inhibition of Burkitt's lymphoma RAMOS cells without significant cytotoxicity in non-BTK cancerous and non-cancerous cell lines. Further, PID-4 showed promising activity in inhibiting BTK and downstream signalling cascades. As a potent inhibitor of Burkitt's lymphoma cells, PID-4 is a promising lead for developing novel chemotherapeutics.
Keywords: Oxindole sulfonamide; Tyrosine Kinase Inhibitors; sulfonamidy; proteinkinasa BTK; Protein Kinase Inhibitors; Humans; Bruton's tyrosine kinase; B-cell malignancies; Cytotoxicity; inhibitory proteinkinas; lidé; inhibitory tyrosinkinasy; Sulfonamides; Antiproliferation; Agammaglobulinaemia Tyrosine Kinase; Knoevenagel condensation; Burkitt Lymphoma; Burkittův lymfom